Terra Nullius, or space precedes place - Diogo De Carvalho, Paula C.S.R., 1977- (2019)
Terra Nullius was a term created by international law to define territories that belonged to no one and could, therefore, be occupied and declared as “new” territory. Etymologically it means no man's land, a land without owner, land that cannot be claimed, ground zero. In Terra Nullius: A Journey Through In One's Land, Sven Linquivist explains how this term was used to justify what has only recently begun to be called genocide. Terra Nullius also has a poetic meaning. An idea of uncharted and unclaimed territory, a kind of oasis of freedom where it would be possible to restart and rethink our idea of society. The performance TERRA NULLIUS proposes both an inner and outer journey, a reflection on what binds us to places, relocating questions about autonomy and demarcation of a cultural or personal identity. If we were allowed to go back to ground zero could we do everything differently? Or hopelessly the same? TERRA NULLIUS it's a hybrid performance project that tries to capture the experience of a year spent in Iceland, putting it in dialogue with distant places and realities, creating overlaps and connections. The public is invited to wander freely inside and outside while listening to an audio patchwork of collective and personal narratives. Using the act of walking as a procedure in itself, the project will have different development stages in 2019/20. - Calouste Gulbenkian Foundation - Cultural Fund of GDA Foundation This is the text published in MFA 2029 final publication and images from the live performance work.